1994
DOI: 10.1055/s-2007-1009026
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Tract Strictures after Orthotopic Liver Transplantation: Diagnosis and Management

Abstract: Biliary tract complications in 105 patients who had undergone orthotopic liver transplantation were reviewed in order to determine their incidence and localization. In addition, the possible endoscopic and percutaneous management of such complications was evaluated. Signs of cholestasis appeared in 32 of 105 (30.5%) transplant recipients after a mean of 6.5 months (range 1-19 months), and visualization of the biliary system was performed in all. Twenty biliary tract complications were observed in these 32 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 0 publications
2
46
0
3
Order By: Relevance
“…The prevalence rate for biliary complications in the study group was 21.43%, which was within the range of 10-30% that has been observed in the studies published on this topic so far [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The prevalence rate for biliary complications in the study group was 21.43%, which was within the range of 10-30% that has been observed in the studies published on this topic so far [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Discussionsupporting
confidence: 56%
“…Among these, biliary complications have been highlighted, with incidence rates ranging from 1 to 50% in different published series, and mostly between 10 and 30% [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . The postoperative period following orthotopic liver transplantation (OLT) is a challenge for transplantation teams, because the clinical and laboratory manifestations of the various potential complications from this procedure present a high degree of overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, others have described successful treatment of NAS with a number of modalities. 3,[14][15][16][17] We did not study the success of treatment in these patients because the group of patients treated with therapeutic ERCP, PTCD, or surgery was too small (28 cases), the group was heterogeneous concerning location and severity of abnormalities, and several types of treatment modalities were used. However, in most patients, an improvement in liver test results was seen, although this is not synonymous with uneventful longterm outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen had to be admitted repeatedly for recurrent bacterial cholangitis (defined as 3 or more episodes). The median number of cholangitis episodes in these 19 was 5 (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Thirty patients were placed on maintenance antibiotic therapy, mostly ciprofloxacin, for some time.…”
Section: Cholangitis Episodesmentioning
confidence: 99%
“…Owing to prognostic and therapeutic implications, extrahepatic lesions (type I) are distinguished from intrahepatic (type II) or a combination of intra-and extrahepatic abnormalities (62,63). Since mainly the extent of intrahepatic alterations is relevant for the treatment success ( Figure 5), Buis et al have suggested a classification of the involved intrahepatic zones A to D (54), Figure 3).…”
Section: Classification Of Nasmentioning
confidence: 99%